Status Sosial Aspek Strata Pendidikan Dalam Pemilihan Umum Presiden 2024 di Kabupaten Deli Serdang - Syafrizal, Syafrizal (Universitas Muhammadiyah Sumatera Utara, 2024)
This article is the result of in-depth research and observation of the last general election process, especially of voter behavior in the presidential election. The excitement that occurs with the presidential debate is a political education that must be appreciated and placed at the level of high-value political education in society. It is realized that many factors influence a person's political choices, perhaps due to close tribal history, religion, hierarchical friendships, and sometimes even gender bias. However, of the many factors that can be considered as factors that influence a person's choice, the researcher chose one aspect, namely the social status aspect, the educational strata aspect of the voter. The various data required were obtained through interviews with several selected informants using qualitative analysis. In general, it turns out that the social status aspect of educational strata is considered to contribute quite a lot in determining voters in the 2024 presidential election in the Deli Serdang Regency area.